The role of NLRP3 inflammasome in multiple sclerosis: pathogenesis and pharmacological application - Zhang, Wen-Gang; Zheng, Xiao-Rui; Yao, Yi; Sun, Wei-Jia; Shao, Bo-Zong (Frontiers in Immunology, 2025)
Multiple sclerosis (MS) is widely acknowledged as a chronic inflammatory autoimmune disorder characterized by central nervous system (CNS) demyelination and neurodegeneration. The hyperactivation of immune and inflammatory responses is recognized as a pivotal factor contributing to the pathogenesis and progression of MS. Among various immune and inflammatory reactions, researchers have increasingly focused on the inflammasome, a complex of proteins. The initiation and activation of the inflammasome are intricately involved in the onset of MS. Notably, the NLRP3 inflammasome, the most extensively studied member of the inflammasome complex, is closely linked with MS. This review will delve into the roles of the NLRP3 inflammasome in the pathogenesis and progression of MS. Additionally, therapeutic strategies targeting the NLRP3 inflammasome for the treatment of MS, including natural compounds, autophagy regulators, and other small molecular compounds, will be detailed in this review.